EKSISTENSI TPA DAN PESANTREN SEBAGAI DASAR DAKWAH YANG IDEAL - Nonci, M. Hajir (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2022)
Da'wah skills should go through scientific stages, especially knowledge related to religious foundations, one of which is very important is reading the Koran properly. Then the basic training is performing preaching with all style and tone of voice. Islamic boarding schools are places that are known as special houses for learning to read the Qur'an starting at the elementary level (iqra') continuing at Islamic boarding schools for tahfiz and tahsin. In addition, they have also begun to be trained in preaching (lecturing). Behavior and personality as preachers have been formed little by little. How to dress, look is not disappointing. Therefore, one of the ideal preaching skill leveling strategies should be from TPA and Islamic Boarding Schools.